Behavioral assessment and faded bedtime intervention for delayed sleep-onset in an adult with autism spectrum disorder. (3rd September 2022) - Luiselli, James K.; Harper, Jill M.; Leach, Matthew; Murphy, Kerrianne J.; Luke, Katherine
Abstract : Faded bedtime has been evaluated as a behavioral intervention for delayed sleep-onset principally with children and youth who have intellectual and developmental disabilities in hospital and home settings. The present case report describes behavioral assessment and faded bedtime intervention in a 21-year old adult man with autism spectrum disorder at a community-based group home. The study also documented the effects of family home visits on the man's sleep when he returned to the group home. Compared to a pre-intervention (baseline) phase, faded bedtime was associated with increased intervals of recorded sleep and a decrease in sleep-onset latency over several months of implementation. We discuss clinical implications of the case and generality of findings across populations and settings.